ARSITEKTUR TRADISIONAL BALI PADA BANGUNAN PURI SEBAGAI DAYA TARIK WISATA MINAT KHUSUS DALAM MENDUKUNG PENGEMBANGAN PARIWISATA BERKELANJUTAN DI BALI - NI MADE AYU NATIH WIDHIARINI; PUTU ENI OKTAVIAN; NI PUTU FEBY DEVIRA PERMANITA (Politeknik Pariwisata Makassar, 2019)
The existence of the castle or puri as a historical and cultural heritage of traditional Balinese architecture at this time began to fade due to the influence of modernization. Not a few puri in Bali have experienced commodification both in terms of shape, function and meaning. Therefore an effort is needed to maintain the continuity of traditional Balinese architecture in the castle building in the midst of global culture, namely by developing the castle towards special interest tourism which is currently becoming a trend in the tourism world. The purpose of this study is to identify the potential of traditional Balinese architecture in castle buildings as a tourist attraction of special interest in supporting the development of tourism in Bali. This research included descriptive qualitative research conducted for three months at Puri Kaba-Kaba, Tabanan, Bali. Data collection was carried out through participatory observation on traditional Balinese architecture in Puri Kaba-Kaba, in-depth interviews with four informants consisting of castle leaders, tourism conscious groups, and the Head of Kaba-Kaba Village, as well as documentation studies of relevant literature and documents. The results of the study show that Puri Kaba-Kaba still preserves the concept of Sanga Mandala especially in parts of sacred or infused places that contain form, function, and meaning of traditional Balinese architecture that is unique and of historical value so that it has the potential to be developed into a special interest tourist attraction.